2008
DOI: 10.4049/jimmunol.181.2.1491
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunomodulatory Properties of Berbamine through Selective Down-Regulation of STAT4 and Action of IFN-γ in Experimental Autoimmune Encephalomyelitis

Abstract: Berbamine (BM) is an herbal compound derived from Berberis vulgaris L commonly used in traditional Chinese medicine. In this study, we show that BM has potent anti-inflammatory properties through novel regulatory mechanisms, leading to reduced encephalitogenic T cell responses and amelioration of experimental autoimmune encephalomyelitis (EAE). The treatment effect of BM was attributable to its selective inhibitory effect on the production and action of IFN-γ in CD4+ T cells, which was mediated through altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…Ren et al (32) found that berbamine targets STAT4 via a ubiquitinprotein isopeptide ligase resulting in decreased production of IFN␥ in CD4 ϩ T cells of experimental autoimmune encephalomyelitis mice, whereas the secretion of IL-17 was not markedly altered. In our study, berberine inhibited the production of both IFN␥ and IL-17 in NOD mice probably as a result of structural differences between berberine and berbamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al (32) found that berbamine targets STAT4 via a ubiquitinprotein isopeptide ligase resulting in decreased production of IFN␥ in CD4 ϩ T cells of experimental autoimmune encephalomyelitis mice, whereas the secretion of IL-17 was not markedly altered. In our study, berberine inhibited the production of both IFN␥ and IL-17 in NOD mice probably as a result of structural differences between berberine and berbamine.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine Significantly Decreases the Production of Inflammatory Cytokines in NOD Mice-Previous studies have indicated that the administration of berberine up-regulates the expression of IL-10 (25) and down-regulates inflammatory cytokines, including IFN␥, TNF␣, and IL-1␤, but had limited effect on IL-17 production (23,24,27,32) in various animal models. To examine whether berberine affected the cytokine profile in this murine model of type 1 diabetes, splenocytes were isolated from vehicle-or berberine-treated NOD mice and were stimulated with ␣-CD3 antibody at the indicated concentration for 48 h. The cytokine profile of the supernatant showed a dramatic decrease in inflammatory cytokines, including IL-17, IL-6, IFN␥, and TNF␣ (Fig.…”
Section: Berberine Delayed the Onset Of Type 1 Diabetes In Nod Mice-mentioning
confidence: 99%
“…Furthermore, Th17 cells are implicated in this model and in several other autoimmune diseases. Although some autoimmune responses formerly attributed to Th1 cells are now believed to be mediated by Th17 cells, recent studies [5][6][7][8][9] continue to emphasize the importance of Th1 cells in EAE development. In fact, EAE can be induced by transfer of either Th17 or Th1 cells.…”
Section: Multiple Sclerosis (Ms) Is a T-cell-mediated Inflammatory Aumentioning
confidence: 99%
“…Cells were directly lysed in SDS sample buffer, and Western blot analysis was conducted as previously described (38). Abs were purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Immunoblot Analysismentioning
confidence: 99%